Inbound marketing funciona? A influência do marketing de conteúdo digital e de mídia on-line em um funil B2B - Cristiane Gontijo Araújo (2021)
The new technologies, favored by the growth of the internet, are pushing consumers and companies to constantly adapt to use current resources to their advantage. In the scenario of business-to-business marketing (B2B), the reality isn't different. Even though the buying process follows similar steps to those established decades ago, the current scenario brings more possibilities and challenges. There are more communication channels available and prospects sometimes prefer to go their own way autonomously and only ask for assistance from suppliers when they have already made their decision. The dynamics of producing and distributing content on the internet has become an imperative for the success of many businesses. In this context, the present study aimed to measure the influence of Digital Content Marketing, exploring the impact of different types of content and media in changing the stage from lead to sales opportunity in a B2B marketing funnel over time. The research was conducted from the analysis of a secondary database, originated on marketing and sales softwares between March 2018 and February 2020. The data were analyzed using Cox Regression, since it is an appropriate method to explain the influence of independent variables on the occurrence of an event over time. The following variables were evaluated: conversion on top of funnel content; conversion on middle of funnel content; conversion on bottom of funnel content; conversion via owned media; conversion via earned media; conversion via paid media; total conversions; imported leads; and the lead ́s position in the company, these being the independent variables, and the variable response the probability of changing from the qualified lead stage to a sales opportunity over time. With the exception of the variables conversion on middle of funnel content and conversion via owned media, all variables impacted the analyzed funnel. This study is expected to contribute to the understanding of this marketing practice, collaborating both in a theoretical perspective, especially in B2B and digital marketing, through the proposed theoretical model and the results found, and in a managerial perspective, with insights for better allocation of marketing resources.